FIND OF EARLY PLANKTONIC FORAMINIFERS IN THE TRIASSIC OF THE CRIMEA - Korchagin O.A.; Kuznetsova K.I.; Bragin N.Yu. (My University, 2003)
The appearance of planktonic foraminifers is the most dramatic episode in the evolution of Protozoans and an important event in the development of the biosphere during the last 400 Ma. Data on initial stages of the development of planktonic foraminifers are far from being complete, which hampers reliable dating of their evolution [1, 3-5, 8, 9].
Keywords: Triassic; Mesozoic::Triassic; Мезозой::Триасовая